Patient-initiated violence against dental staff: a survey in faculty clinic settings - Fux-Noy, Avia; Getter, Oriane; Shmueli, Aviv; Halperson, Elinor; Moskovitz, Moti (Frontiers in Public Health, 2025)
BackgroundWorkplace violence against healthcare personnel is an increasing concern. However, there is limited research on this issue within the dental field.AimThis study aimed to examine the prevalence and characteristics of patient-initiated violence against dental staff.MethodsA cross-sectional survey design was utilized, involving a convenience sample of dental clinic staff at Hadassah Medical Center, Jerusalem, Israel. Participants filled out an anonymous questionnaire that assessed patient aggression in three categories: physical violence, verbal abuse, and reputational harm. Additionally, demographic information such as gender, age, role, and years of experience was collected.ResultsThe response rate was 29%. Of the 103 respondents, 73% were females, 79% were dentists; 95% reported experiencing verbal violence, 27% physical violence, and 53% reputational harm at least once in their career. Male staff reported significantly higher rates of reputational harm compared to female staff (p = 0.025). Dentists experienced significantly more reputational harm than dental auxiliaries (p = 0.004). No significant differences were found based on clinic specialization or years of experience.ConclusionDental clinic staff frequently experience high levels of verbal, physical, and reputational violence. It is essential to conduct larger, nationally representative studies in Israel to confirm these findings. Future research should examine the causes and consequences of patient-initiated violence and explore effective prevention and intervention strategies.